Atopic dermatitis complicated by herpes-like streptococcal infection and subsequently turned into psoriasis. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A baby girl was first observed at the age of 1 year with atopic dermatitis complicated by erysipelas. The patient also presented herpes-like lesions around the right ear and on the thumb, interpreted as herpetic eruption at that moment, but later on, according to the data of the relevant literature, retrospectively diagnosed as herpes-like streptococcal infection. In the following years psoriatic lesions appeared besides the eczematous lesions or in their same place in different times. The appearance of Crohn’s disease and serum negative arthritis confirmed the presence of psoriasis.